2018
DOI: 10.1101/453993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Red squirrels mitigate costs of territory defence through social plasticity

Abstract: 19For territorial species, the ability to be behaviourally plastic in response to changes in their social 20 environment may be beneficial by allowing individuals to mitigate conflict with conspecifics and 21 reduce the costs of territoriality. Here we investigated whether North American red squirrels 22 hoc analyses revealed that evidence of social plasticity in this system was primarily due to 32 within-individual changes in behaviour, which we were unable to estimate in the cross-sectional 33data. Our resul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…During the fall, the pressure exerted by the red squirrels present in the release area was intensified, where resident animals were exploring the enclosure and were making territorial calls from the top of the enclosure directly towards the translocated animals within the enclosure. This solitary territorial species benefits from having stable neighbours (72), at a point where animals avoid settlement in new empty middens even when they occupy poorer quality territories (73). For this reason, translocating single animals can cause the disruption of social relationship with territorial neighbours, which could have an impact on survival and behavior of translocated animals (74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the fall, the pressure exerted by the red squirrels present in the release area was intensified, where resident animals were exploring the enclosure and were making territorial calls from the top of the enclosure directly towards the translocated animals within the enclosure. This solitary territorial species benefits from having stable neighbours (72), at a point where animals avoid settlement in new empty middens even when they occupy poorer quality territories (73). For this reason, translocating single animals can cause the disruption of social relationship with territorial neighbours, which could have an impact on survival and behavior of translocated animals (74).…”
Section: Discussionmentioning
confidence: 99%
“…Red squirrels can maintain the same territory throughout their life, and consequently often choose territory sites close to familiar neighbours (63,65). Red squirrels with familiar neighbours reduced rates of territorial rattle calls and increased time spent in the nest (76). Therefore, considering the composition of the group to translocate can influence survival.…”
Section: Discussionmentioning
confidence: 99%
“…Following natal dispersal, individuals rarely relocate to a vacant territory (25), allowing for the establishment of 20 long-term familiarity among neighbouring individuals. Despite the fact that relationships with territory neighbours are primarily antagonistic, living near familiar neighbours provides important benefits for red squirrels, including reducing the risk of territory intrusion (26) and time spent on territory defence (27).…”
Section: Main Textmentioning
confidence: 99%
“…1, 2; Table 1). 5 We hypothesized that this large observed increase in siring success associated with social familiarity could result either from increased energetic resources (26,27) that allow male squirrels in familiar social neighbourhoods to travel farther to obtain mating opportunities (30,31), or that social familiarity might directly benefit males through increased mating success within their more familiar social neighbourhoods. Analysis of the spatial locations of male 10 paternity success revealed that males traveled farther to mate as familiarity with neighbours increased (β = 19.93 ± 8.83, t = 2.26, P =0.03; Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation